1994
DOI: 10.1073/pnas.91.2.529
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and RU486: opposing effects on human sperm.

Abstract: Progesterone induced a rapid influx of calcium in capacitated human sperm, followed by a long-lasting, dose-dependent increase of intracellular free calcium. Thereafter, progesterone increased the fraction of hyperactivated sperm and the acrosome reaction. On the contrary, the progesterone antagonist RU486 (mifepristone) induced an immediate and transient, dose-dependent decrease of intracellular free calcium and a drop in the values of sperm movement parameters related to hyperactivation. Moreover, RU486 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 26 publications
6
67
0
Order By: Relevance
“…A positive effect of P (0.1-1 m) on forward (Contreras and Llanos, 2001) and hyperactivated (Uhler et al, 1992;Calogero et al, 1996;Jaiswal et al, 1999) motility has been reported by some authors but not confirmed by others (Kay et al, 1994;Wang et al, 2001;Luconi et al, 2004). The effect of P on hyperactivated motility was found to be transient and was not counteracted by P antagonists (Uhler et al, 1992;Yang et al, 1994). Recently, it has been found that P induces Ca 2+ oscillations, due to a release from intracellular stores (see also next) in the proximity of the flagellum, which are strictly related to the flagellar activity (Harper et al, 2004;Bedu-Addo et al, 2007), suggesting that this mechanism, rather than the massive Ca 2+ entry stimulated by the steroid, is responsible for induction of hyperactivation.…”
Section: P-induced Sperm Motilitymentioning
confidence: 86%
“…A positive effect of P (0.1-1 m) on forward (Contreras and Llanos, 2001) and hyperactivated (Uhler et al, 1992;Calogero et al, 1996;Jaiswal et al, 1999) motility has been reported by some authors but not confirmed by others (Kay et al, 1994;Wang et al, 2001;Luconi et al, 2004). The effect of P on hyperactivated motility was found to be transient and was not counteracted by P antagonists (Uhler et al, 1992;Yang et al, 1994). Recently, it has been found that P induces Ca 2+ oscillations, due to a release from intracellular stores (see also next) in the proximity of the flagellum, which are strictly related to the flagellar activity (Harper et al, 2004;Bedu-Addo et al, 2007), suggesting that this mechanism, rather than the massive Ca 2+ entry stimulated by the steroid, is responsible for induction of hyperactivation.…”
Section: P-induced Sperm Motilitymentioning
confidence: 86%
“…Therefore, we performed an inhibitor study using the potent antiprogestin, RU486. RU486 inhibits calcium uptake in sperm and counteracts the stimulation that is produced by progesterone (Yang et al, 1994). The rationale for using the inhibitor of progesterone to determine whether or not the acrosome reaction is the result of a specific progesterone action was that antiprogestin reverses the progesterone effects by competing with the binding sites of progesterone, assuming that progesterone induces the acrosome reaction through its specific receptors in spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase C (PLC; Fukami et al 2003) and/or protein kinase A (Harrison et al 2000) are involved in progesteroneinduced AR. Progesterone also changes motility parameters (Yang et al 1994) and enhances hyperactivation in human (Sueldo et al 1993) and hamster spermatozoa (Noguchi et al 2008). Although progesterone enhances hyperactivation of human and hamster spermatozoa (Sueldo et al 1993, Noguchi et al 2008, the effective concentration of progesterone is different between humans and hamsters.…”
Section: Introductionmentioning
confidence: 99%